PENERAPAN KONSELING KELOMPOK DALAM PENDAMPINGAN PSIKOLOGIS KOMUNITAS ORANG DENGAN AUTOIMUN (KOMUNITAS ODAI) - Widya Risnawaty; Michelle Gabriel Hudian Putri; Renata Verla Gunjaya (PROSIDING SERINA, 2021)
The number of people with autoimmune diseases is increasing from year to year. Autoimmune diseases are classified as diseases that can cause death. Therefore it needs to get more serious attention. Autoimmune disease occurs when a person's immune system attacks its own body tissues. Vulnerability in immunity makes sufferers experience various impacts, both physically and psychologically. Changes in physical conditions that are generally experienced by people with autoimmune diseases. The existence of these physical conditions triggers a decrease in psychological conditions. Vice versa, psychological changes further worsen the physical condition. In addition, in their daily life they have to struggle to continuously adjust to their body condition, the demands of their family and the environment. Autoimmune sufferers need to maintain the stability of their psychological condition. In this PKM activity, the PKM team in collaboration with the ODAI Community intends to provide psychological assistance in the form of group counseling activities. This group counseling activity is a form of intervention aimed at helping ODAI community members learn to manage their stress so as to minimize flares. This group counseling activity will involve 10 members of the ODAI Community who are in the age range of 17 – 31 years. Group counseling is carried out in 3 sessions. Evaluation of the results of the application of group counseling refers to the results of the pretest/posttest and reports of changes experienced by the participants. Group counseling activities are still ongoing so that the results of the implementation cannot be reported in full.